Comparing Some Fundamental Skills According to Skill Performance Level In Soccer Players Aged 15 years old - Gamal, Mohammed (Journal of Physical Education, 2018)
Comparing Some Fundamental Skills According to Skill Performance Level In Soccer Players Aged 15 years oldThe importance of the research lies in the athletes' level of performing fundamental soccer skill. The researcher used the descriptive method. The subjects were (30) soccer players aged 15 years old from the national soccer center in Baghdad. The variables were selected and the main experiment was applied followed by data collection, display and discussion. The researcher concluded that fundamental skills have a great effect on soccer players' skill performance level. Finally the researcher recommended paying attention to soccer fundamental skills due to their great effect on skill performance level.